Correlation between antibiotic susceptibilities and genotypes in Neisseria gonorrhoeae from different geographical origins: determinants monitoring by real-time PCR as a complementary tool for surveillance. Issue 2 (1st November 2009) - Vernel-Pauillac, Frédérique; Ratsima, Elisoa H; Guillard, Bertrand; Goursaud, Régis; Lethezer, Camille; Hem, Sopheak; Merien, Fabrice; Goarant, Cyrille
Abstract : Objective: To determine in Neisseria gonorrhoeae (NG) isolates from different geographical areas whether monitoring of major determinants involved in chromosomal antimicrobial resistance correlated with phenotypes and could constitute complementary tools for surveillance. Methods: Real-time multiplex PCR assays targeting penA, mtrR, penB, ponA, gyrA and parC determinants were applied to 169 NG extracts. Minimum inhibitory concentrations for penicillin and ciprofloxacin were determined by E tests, and β-lactamase production was analysed using nitrocefin discs. Results: A total of 169 NGs were examined, 110 from New Caledonia, 44 from Madagascar and 15 from Cambodia. Despite the heterogeneity in the number of isolates tested, the susceptibility trends observed in the different geographic areas studied showed a good fit with the multigene genotypes. In addition, features related to a specific geographical diversity were found: (1) a high prevalence of strains harbouring the porB1a allele and showing reduced penicillin susceptibility in Madagascar and Cambodia (39% and 40% respectively); (2) almost all strains from Cambodia were resistant to the drugs tested (11/15 and 14/15 resistant to penicillin and ciprofloxacin respectively); and (3) identification of novel penB and mtrR genotypes associated with a moderately decreased penicillin susceptibility in New Caledonia ( mtrR novel genotype in 47% of intermediate vs 14% of susceptible isolates). Conclusions: Showing a good correlation with phenotypic trends of susceptibility, multiplex real-time PCR assays could be used successfully for prospective epidemiological studies notably by characterising mtrR and penB determinants for their fundamental and complementary roles in increasing the antibiotic resistance. These molecular tools could also provide useful alternative surveillance tools for non-viable strains.